A panel data model of length of stay in hospitals for hip replacements. (9th August 2021) - Meng, Yan; Gao, Jiti; Zhang, Xibin; Zhao, Xueyan
Abstract: Inequality between private and public patients in Australia has been an ongoing concern due to its two tiered insurance system. This article investigates the variations in hospital length of stay for hip replacements using the Victorian Admitted Episodes Dataset from 2003/2004 to 2014/2015, employing a Bayesian hierarchical random coefficients model with trend. We find systematic differences in the length of stay between public and private hospitals, after observable patient complexity is controlled. This suggests shorter stays in public hospitals due to pressure from the Activity-based funding scheme, and longer stays in private system due to potential moral hazard. Our counterfactual analysis shows that public patients stay 1.8 days shorter than private patients in 2014, which leads to the "quicker but sicker" concern that is commonly voiced by the public. We also identify widespread variations among individual hospitals. Sources for such variation warrant closer investigation by policy makers.